Effectiveness of the flipped classroom versus the traditional teaching method in enhancing learning among undergraduate medical students - Dipti Mohapatra; Arati Meher; Prakash Kumar Sahoo; Tapaswini Mishra; Arati Mohanty (Bangabandhu Sheikh Mujib Medical University Journal)
Background: The flipped classroom is a form of interactive teaching strategy in which traditional learning is reversed by delivering core content outside the classroom and moving activities into the classroom. This study aimed to determine the effectiveness and medical students’ perception of flipped classroom.